Total Correction of Tetralogy of Fallot in the First 60 Days of Life in Symptomatic Infants: Is It The Gold Standard? - Menaissy, Yasser; Omar, Ihab; Mofreh, Basem; Alassal, Mohamed (The Thoracic and Cardiovascular Surgeon, 2020)
Background The timing of surgical repair of tetralogy of Fallot (TOF) is a key to alleviate complications and for long-term survival. Total correction was usually performed at the age of 6 months or older under the notion of decreasing the surgical risk. However, avoiding palliation with an aortopulmonary shunt and early correction of systemic hypoxia appear to be of more benefit than the inborn surgical risk in low body weight patients. Our objective was to assess early/midterm survival and operative complications and to analyze patients, surgical techniques, and morphological risk factors to determine their effects on outcomes.Patients and Methods We retrospectively reviewed 152 patients with TOF who were ≤60 days of age when they underwent total correction of TOF. All patients had either duct-dependent pulmonary blood flow or arterial blood oxygen saturation less than 65% on room air requiring urgent surgical correction. Exclusion criteria included TOF with pulmonary atresia, TOF with nonconfluent pulmonary arteries, TOF with multiple aortopulmonary collateral arteries, and associated complete atrioventricular septal defects.Results The mean age at repair was 34 ± 19 days, and the mean weight was 3.8 ± 0.9 kg. Before surgery, 96 patients received an infusion of prostaglandin, 45 were mechanically ventilated, and 32 required inotropic support. Right ventricular outflow tract obstruction was managed with a transannular patch in 112 patients, and all the others had a main pulmonary artery patch. Cardiopulmonary bypass (CPB) with moderate hypothermia was the standard, and the CPB time averaged 48 ± 21 minutes. The postoperative intensive care unit stay was 5.7 ± 6 days, with 2.8 ± 4 days of mechanical ventilation. Early mortality was 4.6% (7 of 152), and actuarial survival rates were 95% at 1 year and 92% at 5 years. Univariable and multivariable analyses of the patients' demographics, anatomical characteristics, and operative techniques revealed the presence of small pulmonary arteries and low body weight to be the only independent risk factors for death.Conclusion Early total correction of TOF during the first 60 days of life can be performed with low mortality and good intermediate-term survival and, from our point of view, “should be the gold standard for TOFs.”
Keywords: correction of TOF; early age; congenital heart diseases